Dampak pandemi Covid-19 terhadap harga saham dan aktivitas volume perdagangan (Studi kasus saham LQ-45 di Bursa Efek Indonesia) - Febriyanti, Galuh Artika (Universitas Sam Ratulangi, 2020)
The purpose of this research to examine the impact of the Covid-19 on stock prices and trading volume activity on listed firms of Index LQ-45 on the Indonesia Stock Exchange. The first case of the Covid-19 in Indonesia was announced on March 2nd, 2020. This research is to find out whether there are average abnormal returns and transaction volume of the stock company listed in Index LQ-45 before and after of event the first case of the Covid-19 in Indonesia was announced on March 2nd, 2020. These data have been taken for 30 days before and 30 days after the first announcement of Covid-19 in Indonesia. The result of the paired sample test shows that there is a significant difference in the abnormal return of stock company listed in index LQ-45 between before and after the first announcement of the Covid-19 case in Indonesia. This is indicated by the significance value of 0,008 < 0,05 which the stock prices decreased after the first announcement of the Covid-19 case in Indonesia. The volume transaction also shows different significance. The transaction volume after the announcement of shares shows an increasing value.